Expression of EGF-family receptors and amphiregulin in multiple myeloma. Amphiregulin is a growth factor for myeloma cells - Mahtouk, Karène; Hose, Dirk; Rème, Thierry; De Vos, John; Jourdan, Michel; Moreaux, Jérôme; Fiol, Geneviève; Raab, Marc-Steffen; Jourdan, Eric; Grau, Véronique; Moos, Marion; Goldschmidt, Hartmut; et al. (Oncogene, 2005)
A hallmark of plasma cells is the expression of syndecan-1, which has major functions in epithelial cells, in particular as the coreceptor of heparin-binding growth factors. We previously found that heparin-binding epidermal growth factor-like growth factor (HB-EGF) is a growth factor for malignant plasma cells. As amphiregulin (AREG) is another heparin-binding factor of the EGF family, we investigated its role in multiple myeloma (MM). Using Affymetrix DNA microarrays, we show here that the AREG gene was expressed by purified primary myeloma cells from 65 patients and that the expression was higher than in normal bone marrow (BM) plasma cells or plasmablastic cells. AREG stimulated IL-6 production and growth of BM stromal cells. Using real-time reverse transcriptase-polymerase chain reaction, we found that MM cells expressed ErbB receptors and that AREG promoted their growth. Furthermore, PD169540 (a pan-ErbB inhibitor) and IRESSA (an ErbB1-specific inhibitor) induced apoptosis of primary myeloma cells from 10/14 and 4/14 patients, respectively, and there was a synergistic effect with dexamethasone. Altogether, our data provide strong evidence that AREG plays an important role in the biology of MM and emphasize the advantages of using ErbB inhibitors, which might target myeloma cells as well as the tumor environment.